Analysis of Subsurface Faults Using 3D Gravity Method Based On Satellite Image Data: Insights into Indo-Australian and Eurasian Plate Subduction in the Formation of An Accretionary Prism - Kadek Ciptani Satria Dewi; Rahmat Nawi Siregar; Trisna Ikhsan Ningati; Zumaida Nur Pulungan; Agapetalia Indriyawati; Hirotaka Takahashi (International Journal of Hydrological and Environmental for Sustainability, 2025)
This geophysical study employs the gravity method to analyze subsurface fault structures in the Simeulue Island region. The area lies within an active tectonic zone where the Indo-Australian Plate subducts beneath the Eurasian Plate, making it a critical site for understanding subduction dynamics and accretionary prism formation. Secondary gravity and topographic data were acquired from TOPEX satellite imagery. The primary objective is to identify gravity anomalies and delineate subsurface geological features such as faults, folds, and fractures based on variations in the Earth's gravitational field caused by density contrasts between rock units. The gravity method is particularly effective due to its sensitivity to such density differences. Qualitative interpretation was conducted using Surfer 16, while quantitative modeling utilized Oasis Montaj. Results reveal high Bouguer anomaly values in the southwest, corresponding to the plate convergence zone, and low anomaly values extending from the southeast to northwest, associated with the accretionary prism. The 2D model illustrates the subduction of oceanic crust with a density of 3.43 g/cm³ beneath continental crust with a density of 2.67 g/cm³. The 3D model further reveals that subduction becomes evident at a depth of approximately 16.11 km, with the crustal thickness in the accretionary prism zone reaching around 19.92 km. The 3D approach provides a more comprehensive spatial visualization of the subduction geometry and density distribution, offering insights that surpass conventional 2D analysis. These findings contribute to a deeper understanding of regional geodynamics and may serve as a reference for seismotectonic studies and disaster mitigation efforts in the surrounding area.